Pengaruh Antara Religiusitas Dan Emphaty Terhadap Forgiveness Pada Mahasiswa Universitas Islam 45 Bekasi - Nasywa Putri Aurora; Diah Eka Fariska; Rifa Nur Azizah; Lucky Purwantini (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Social interaction has become a crucial need for students in the university environment, but individual conflicts can pose challenges. Conflict is a part of life, but if not handled properly, it can be difficult to control. This research aims to explore the relationship between religiosity and empathy with forgiveness behavior, utilizing a quantitative approach. The research sample involves 135 active students from Universitas Islam 45 Bekasi. The analysis results indicate that there is no significant linear relationship between religiosity and forgiveness, and there is no significant linear relationship between empathy and forgiveness. These findings illustrate that a high level of religiosity does not necessarily indicate positive forgiveness behavior, and empathy does not always contribute to the formation of forgiving attitudes. Additionally, the research highlights other contributing factors to forgiveness not addressed in the study, such as relationship quality, personality types, and attack characteristics. Therefore, further research is needed to identify and measure the influence of these factors. Furthermore, the research results indicate that 88% of other factors influencing forgiveness remain unexplored, emphasizing the need for further research with larger and more diverse samples.